Mitophagy in Antiviral Immunity - Wang, Hongna; Zheng, Yongfeng; Huang, Jieru; Li, Jin (Frontiers in Cell and Developmental Biology, 2021)
Mitochondria are important organelles whose primary function is energy production; in addition, they serve as signaling platforms for apoptosis and antiviral immunity. The central role of mitochondria in oxidative phosphorylation and apoptosis requires their quality to be tightly regulated. Mitophagy is the main cellular process responsible for mitochondrial quality control. It selectively sends damaged or excess mitochondria to the lysosomes for degradation and plays a critical role in maintaining cellular homeostasis. However, increasing evidence shows that viruses utilize mitophagy to promote their survival. Viruses use various strategies to manipulate mitophagy to eliminate critical, mitochondria-localized immune molecules in order to escape host immune attacks. In this paper, we will review the scientific advances in mitophagy in viral infections and summarize how the host immune system responds to viral infection and how viruses manipulate host mitophagy to evade the host immune system.